Critical Success Factors in Intellectual Property Commercialization among Academia - Siti Hajar Arani; Nurul Fadly Habidin; Nur Yuhainis Ab Wahab (International Business Education Journal, 2022)
The commercialization of research is defined as the process of implementing ideas following the development of current innovations. It can also be defined as the process of translating research knowledge to improve the quality of a product or service so as to be able to enter the market. Previous research has suggested that academia should have networks with industry sectors for idea or technology consultation. Academia should also be involved in developing the idea of technology creation from industry so that the product or service produced can meet consumer demand. Specifically, the proposed objectives of this paper are to discuss and identify the critical success factors in intellectual property commercialization among academia. This paper will also discuss the concept, followed by the underpinning theory, conclusions as well as recommendations for future research.